Current status and prospects of robotic right hemicolectomy - Li Taiyuan; He Penghui (结直肠肛门外科)
Robotic right hemicolectomy has been widely carried out both domestically and internationally. Compared to the limitations of laparoscopic surgery, robotic surgery offers more precise and flexible manipulation, especially when performing complex surgeries and intra-abdominal anastomoses. In recent years, various robotic surgery systems have been introduced and applied to surgical procedures both domestically and internationally, bringing new possibilities to the surgical robotics industry. This article aims to elaborate on the development, current status, and future prospects of robotic right hemicolectomy.